ANTESEDEN KEPUASAN TERHADAP LOYALITAS PELANGGAN (Studi Pelanggan KaliMilk di Surakarta) - Dwi Hastjarja Kustijana B., Hilda Nasti Gusma & (Universitas Slamet Riyadi, 2015)
The purpose of this study was to determine the effect of price, quality products, quality service, environment, and customer satisfaction on customer loyalty KaliMilk in Surakarta. The population in this study were individuals who had visited and buy products KaliMilk in Solo and intend to loyal. A sample of 160 respondents were taken by purposive sampling. The technique of collecting data using questionnaires. Hypothesis testing using analytical tools Generalized Structured Component Analysis (GSCA). The study concluded that (1) the price has no effect on customer satisfaction (2) the quality of the products have a significant effect on customer satisfaction (3) significant effect of service quality on customer satisfaction (4) significant environment effect on customer satisfaction (5) customer satisfaction have a significant effect on customer loyalty. This study can be used as a reference for practitioners in the decision to take steps to determine marketing strategies in order to improve quality, customer satisfaction, and establish customer loyalty KaliMilk. Keywords: price, product quality, service quality, environment, customer satisfaction, customer loyalty